Experimental study of overpressure evolution laws and flame propagation characteristics after methane explosion in transversal pipe networks. (25th May 2019) - Niu, Yihui; Shi, Biming; Jiang, Bingyou
Highlights: A transverse pipe network methane explosion experimental system was established. The pressure wave generated by 9.5% methane concentration is higher than 8% and 11%. A high pressure area is created in the middle of the transversal branch. Flame sustaining time and surface damage are minimal at the transversal branch. Abstract: To explore overpressure evolution laws and flame propagation characteristics after methane explosion in a complex pipe network, we established in the lab a transversal pipe network methane explosion experimental system and experimentally studied the explosive pressure wave propagation laws of premixed gases of three different methane concentrations (8%, 9.5%, and 11%). Experimental results indicate that an overpressure rising region will be formed in the transversal branch, which is due to the superposition of pressure waves after methane–air premixed gas explosion. However, the flame intensity generated by pressure wave is extremely small and the flame sustaining time is very short. In the parallel branch, maximum explosion overpressure presents a gradually descending trend, and flame propagation velocity presents a rising and then descending trend, but the flame sustaining time decreases first, then increases, and finally decreases again as the distance from the explosion source increases. The maximum explosion overpressure and flame propagation velocity of the gas with a 9.5% methane concentration are higher than 8% and 11%. The experimental study obtains a preliminary mastery of overpressure evolution laws and flame propagation characteristics after methane explosion in pipe networks. The results could provide important theoretical guidelines for the prevention and control of fuel gas explosion in urban pipe networks.